Alcohol-resistant sporulation mutants of Bacillus subtilis. - Bohin, J P (1982)
About 80% of Bacillus subtilis cells form spores when grown in nutrient broth. In medium containing various short-chain aliphatic alcohols, the frequency of sporulation was reduced to 0.5%. Mutants sporulated in the presence of alcohols at a frequency of 30 to 40%. Sporulation in the wild-type cells was sensitive to alcohol at the beginning of sporulation (stage zero). Sensitivity to alcohol in the mutants was also at stage zero, even though the sensitivity was considerably reduced. This sensitivity of sporulation to alcohol is the phenotypic expression of a genetic locus designated ssa. Mutations at this locus lead to a decreased sensitivity of sporulation to alcohol without modifying the sensitivity of growth. Genetic analysis by transduction was bacteriophage PBS1 revealed that ssa mutations are near the previously described spo0A locus. ssa mutants also differ from wild-type cells in the composition of membrane phospholipids. The relative amount of phosphatidylglycerol increased, whereas the relative amount of phosphatidylethanolamine and lysylphosphatidylglycerol decreased relative to the proportions in the wild type. The distribution of fatty acids in membrane lipids is the same as in the wild type. No differential sensitivity of phospholipid metabolism to alcohol could be detected in the mutant. This work therefore reveals that the extensive, pleiotropic changes in the membranes of ssa mutants are the phenotypic reflection of alterations at a specific gene locus.